Meningkatkan Kemampuan Guru-Guru Dalam Membuat Pertanyaan Menarik Melalui Teknik Bimbingan Kelompok - Lily Mahmud (Student Journal of Early Childhood Education, 2023)
The formulation of the problem in this study is can improve the ability of teachers to make interesting question guidelines in TK Surya 2 Tunggulo Limboto Barat, Gorontalo. This research was carried out in TK Surya 2 Tunggulo Limboto Barat, Gorontalo. This research was carried out for two cycles. Each cycle consists of stages of planning, observation / observance. Action and reflection. The technique of data analysis is to analyze, process, present and draw conclusions. In cycle 1 can be described as good 57%, , enough 28.57% and less 14.29% after being carried out cycle 2 then increases well to 80% and enough 20% and less to 0%. From the results of the research in this activity, it can be concluded that with group guidance techniques carried out by the principal, it can improve the ability of teachers to make guidelines for interesting questions in TK Surya 2 Tunggulo Limboto Barat, Gorontalo.